Characterization of Genomic Variants Associated with Resistance to Bedaquiline and Delamanid in Naive Mycobacterium tuberculosis Clinical Strains - Battaglia, S; Spitaleri, A; Cabibbe, A M; Meehan, C J; Utpatel, C; Ismail, N; Tahseen, S; Skrahina, A; Alikhanova, N; Mostofa Kamal, S M; Barbova, A; Niemann, S; et al. (Journal of clinical microbiology, 2020)
The role of mutations in genes associated with phenotypic resistance to bedaquiline (BDQ) and delamanid (DLM) in complex (MTBc) strains is poorly characterized. A clear understanding of the genetic variants' role is crucial to guide the development of molecular-based drug susceptibility testing (DST). In this work, we analyzed all mutations in candidate genomic regions associated with BDQ- and DLM-resistant phenotypes using a whole-genome sequencing (WGS) data set from a collection of 4,795 MTBc clinical isolates from six countries with a high burden of tuberculosis (TB). From WGS analysis, we identified 61 and 163 unique mutations in genomic regions potentially involved in BDQ- and DLM-resistant phenotypes, respectively. Importantly, all strains were isolated from patients who likely have never been exposed to these medicines. To characterize the role of mutations, we calculated the free energy variation upon mutations in the available protein structures of Ddn (DLM), Fgd1 (DLM), and Rv0678 (BDQ) and performed MIC assays on a subset of MTBc strains carrying mutations to assess their phenotypic effect. The combination of structural and phenotypic data allowed for cataloguing the mutations clearly associated with resistance to BDQ ( = 4) and DLM ( = 35), only two of which were previously described, as well as about a hundred genetic variants without any correlation with resistance. Significantly, these results show that both BDQ and DLM resistance-related mutations are diverse and distributed across the entire region of each gene target, which is of critical importance for the development of comprehensive molecular diagnostic tools.